2009
DOI: 10.1111/j.1365-2621.2009.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genotype, location and baking on the phenolic content and some antioxidant properties of cereal species

Abstract: In order to assess the effect of genotype, location and their interaction on total phenolic content (TPC) of chemical extracts, the whole grains of durum and soft wheat, oat, barley and triticale were evaluated. Data showed differences in phenolic content of chemical extracts among cereal species and the analysis of variance confirmed the key role of location. Besides TPC and trolox equivalent antioxidant capacity (TEAC) values assessed by chemical extraction were compared with those obtained with an in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 37 publications
8
85
1
3
Order By: Relevance
“…Phenolic contents in CB (6.2 mg/100 g) were similar to those previously reported in breads made with white wheat flour methods (3.4 mg/100 g to 11.1 mg/100 g) (Lu et al 2014;Menga et al 2010). The replacement of wheat flour by GP promoted a dose-dependent increase in phenolics contents guava breads (Table 1).…”
Section: Soluble and Insoluble Phenolic Compoundssupporting
confidence: 74%
“…Phenolic contents in CB (6.2 mg/100 g) were similar to those previously reported in breads made with white wheat flour methods (3.4 mg/100 g to 11.1 mg/100 g) (Lu et al 2014;Menga et al 2010). The replacement of wheat flour by GP promoted a dose-dependent increase in phenolics contents guava breads (Table 1).…”
Section: Soluble and Insoluble Phenolic Compoundssupporting
confidence: 74%
“…Significant differences in the content of anthocyanins and carotenoids, and in reducing power were observed between genotypes, and between the different millstreams of the respective plant material. From the results of this study, and from other studies previously carried out (Siebenhandl et al, 2007;Bokore, 2008;Menga et al, 2010) it can be concluded that on the one hand genetic and environmental factors have a major impact on the phytochemical profile and the antioxidant activity, but on the other hand also postharvest treatments such as fractionation of the raw material can have a major influence. Thus, it is anticipated that the development of barley cultivars for human consumption should focus on breeding for specific end uses (Hang et al, 2007).…”
Section: Resultsmentioning
confidence: 59%
“…The release of phenolics in the colon may explain the inverse association between whole-grain consumption and incidence of certain chronic diseases (Andreasen et al, 2001;Kern et al, 2003). Moreover, an apparent increase of antioxidant release during enzymatic incubation was found in in vitro studies (Pérez-Jiménez & Saura-Calixto, 2005;Nagah & Seal, 2005;Menga et al, 2010).…”
Section: Phytochemicals In Barleymentioning
confidence: 96%
See 1 more Smart Citation
“…However for grass pea, the trend was not the same, as grass pea showed significant effects of variety only for TPC and HTC, and significant effects of environment only for TFC and CTC, and for interaction between year × row only for CTC (p < 0.001). No reports are available in the literature related to these findings, although effects of environment on phenolics have been indicated in several studies on cereals, fruit and pulses under conventional farming [40][41][42]. According to the results from the present study, lentils are more receptive than grass pea to environment changes, as shown for all of the modified antioxidant compounds studied here.…”
Section: Antioxidant Compounds and Antioxidant Activitymentioning
confidence: 49%